The Pectoralis Major Myocutaneous Flap - Teo, Ken G. W.; Rozen, Warren M.; Acosta, Rafael (Journal of Reconstructive Microsurgery, 2013)
Introduction The pectoralis major myocutaneous flap (PMMF) is a workhorse flap for head and neck reconstruction and a flap of choice for anterior chest wall reconstruction.Methods A thorough review of the literature was undertaken, exploring the full range of designs, variations, indications, and outcomes of the PMMF.Results Numerous modifications have been documented since it was first described in 1968. Complication rates vary greatly in the literature, but most institutions describe significant success with the PMMF. It is fast, versatile, reliable, and a good alternative when microsurgical flap failure occurs. A classification system of skin paddles is presented.Conclusion In the era of free tissue transfer, the PMMF still has its advantages and continues to command an important place in the reconstructive surgeon's armamentarium.
Keywords: pectoralis major; myocutaneous; pedicled; flap; reconstruction